Changes in epileptogenicity biomarkers after stereotactic thermocoagulation. (17th July 2021) - Contento, Margherita; Pizzo, Francesca; López‐Madrona, Víctor J.; Lagarde, Stanislas; Makhalova, Julia; Trébuchon, Agnes; Medina Villalon, Samuel; Giusiano, Bernard; Scavarda, Didier; Carron, Romain; Roehri, Nicolas; Bénar, Christian‐George; et al.
Abstract: Objective: Stereo‐electroencephalography (SEEG)‐guided radiofrequency thermocoagulation (RF‐TC) aims at modifying epileptogenic networks to reduce seizure frequency. High‐frequency oscillations (HFOs), spikes, and cross‐rate are quantifiable epileptogenic biomarkers. In this study, we sought to evaluate, using SEEG signals recorded before and after thermocoagulation, whether a variation in these markers is related to the therapeutic effect of this procedure and to the outcome of surgery. Methods: Interictal segments of SEEG signals were analyzed in 38 patients during presurgical evaluation. We used an automatized method to quantify the rate of spikes, rate of HFOs, and cross‐rate (a measure combining spikes and HFOs) before and after thermocoagulation. We analyzed the differences both at an individual level with a surrogate approach and at a group level with analysis of variance. We then evaluated the correlation between these variations and the clinical response to RF‐TC and to subsequent resective surgery. Results: After thermocoagulation, 19 patients showed a clinical improvement. At the individual level, clinically improved patients more frequently had a reduction in spikes and cross‐rate in the epileptogenic zone than patients without clinical improvement ( p = .002, p = .02). At a group level, there was a greater decrease of HFOs in epileptogenic and thermocoagulated zones in patients with clinical improvement ( p < .05) compared to those with no clinical benefit. Eventually, a significant decrease of all the markers after RF‐TC was found in patients with a favorable outcome of resective surgery (spikes, p = .026; HFOs, p = .03; cross‐rate, p = .03). Significance: Quantified changes in the rate of spikes, rate of HFOs, and cross‐rate can be observed after thermocoagulation, and the reduction of these markers correlates with a favorable clinical outcome after RF‐TC and with successful resective surgery. This may suggest that interictal biomarker modifications after RF‐TC can be clinically used to predict the effectiveness of the thermocoagulation procedure and the outcome of resective surgery.